Physical therapist clinical reasoning in home care for walking assistive device prescription: A description of practice. (2nd January 2023) - O'Brien, Suzanne R.; Barry, Meghan; Davidson, Emily; Porzi, Lauren; Spink, Makenzi; Weatherbee, Danae
ABSTRACT: Background: Home care in the United States (US) provides rehabilitative care to people who are homebound after acute hospitalization. Patients with stroke and brain injury (BI) are commonly seen by physical therapists (PTs/PTAs), who often address the loss of walking independence. Clinical reasoning (CR) is required for walking assistive device (WAD) prescription within the home. There has never been a description of the home care PT CR process, which could inform entry-level training and health policy. Purpose: To describe the homecare CR process by identifying factors used for prescription of WADs in patients with stroke and BI. Secondly, to describe any practice issues associated with WADs. Methods: Directors of 7 agencies affiliated with Nazareth College DPT program were recruited to identify PTs/PTAs to complete an online survey between March – July 2017. Quantitative and qualitative data were collected, and analyzed for frequencies or for common themes. Results: A total of 334 PTs/PTAs were enrolled from all agencies and 72 responses were analyzed. The CR process did not differ between stroke and BI. Safety was the primary factor, which was assessed by patient query, observation skills, and objective measures. PTs/PTAs also measured balance, strength, function, cognition, and patient preferences within the context of the home. WADs obtained prior to initiation of home care often weren't used. Conclusion: A complex CR process has been described for WAD prescription in home care for patients with stroke and BI. Entry-level training and health policy implications are described.